Shape, Share, Showcase: Exploring Digital Narratives of "Ekspedisi Patriot" in Teluk Wondama, West Papua, through Instagram @patriotwondama - Alyatalatthaf, Muhammad Dicka Ma'arief; Muhamad Latif, Mubdi; Setiadi, Kusumajaya; Frissa Sofia, Adhima; Shine Nauli Natasha, Simanjuntak (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
The idea of developing a region in Indonesia goes beyond building infrastructure, it also involves fostering morale, education, and the cultivation of a positive public opinion. The establishment of such a positive image can be achieved through the use of contemporary popular media, one of which is Instagram. This study aims to explore the digital narrative of the Ekspedisi Patriot program in Teluk Wondama, West Papua, as represented through the Instagram account @patriotwondama. The research adopts a qualitative framework with an artistic research methodology, focusing on the process of creative production. The findings indicate that the content production of @patriotwondama is carried out through the Shape strategy (pre-production, production, and post-production), which is applied across Instagram posts, stories, and reels. The Share phase involves creating engaging content in various formats, collaborating with other creators, ensuring content relevance, avoiding repetitive reposts, and monitoring content insights. The Showcase stage focuses on expressing institutional identity and values, emphasizing Indonesian aspects and socio-cultural positioning that stimulate the audience through the integration of pop culture and traditional culture.